Reducing stigma and increasing competence working with mental illness: Adaptation of a contact-based program for osteopathic medical students to a virtual, active learning format - Julia R. Van Liew; Chunfa Jie; Jeritt R. Tucker; Lisa Streyffeler (Medical Education Online, 2023)
ABSTRACTPurpose Contact-based education, offering meaningful contact with individuals living in recovery with mental illness, reduces stigma. This study evaluated the effectiveness of the National Alliance on Mental Illness Provider Education Program (NAMI PEP) when implemented as a curricular requirement across two cohorts of third-year osteopathic medical students, comparing traditional, passive learning and active, online delivery formats.Materials and Methods Participants were two cohorts of third-year medical students (Cohort 1 n = 186; Cohort 2 n = 139; overall N = 325) who completed questionnaires measuring affect, beliefs, and behaviors toward patients with mental illness at pre-program, 1-week follow-up, and 6-month follow-up. For Cohort 1, the existing community-based NAMI PEP was implemented. For Cohort 2, the program was adapted to an online, active learning format tailored to medical students, and an additional 3-month follow-up assessment was added to better identify intermediate-term effects.Results The NAMI PEP was associated with longitudinal improvements in target outcomes, with enhanced effects with the adapted curriculum in Cohort 2. At 6-month follow-up, students reported less stigma, fewer stereotyping negative attitudes, and lower anxiety treating patients with mental illness. They also reported increased confidence integrating psychiatry into routine care and increased competence in principles of collaborative mental health treatment.Conclusions This study demonstrates the longitudinal effectiveness of the NAMI PEP across two cohorts of medical students, with strengthened effects observed when the program is tailored to contemporary medical education.